Biomechanics of sclera crosslinked using genipin in rabbit - Liu, Tai-Xiang (Int J Ophthalmol, 2017)
AIM: To strengthen the biomechanics of collagen by crosslinking rabbit scleral collagen with genipin to develop a new therapy for preventing myopic progression. METHODS: Ten New Zealand rabbits were treated with 0.5 mmol/L genipin injected into the sub-Tenon's capsule in the right eyes. Untreated contralateral eyes served as the control. The treated area was cut into scleral strips measuring 4.0 mm×10.0 mm for stress-strain measurements (n=5). The remaining five treated eyes were prepared for histological examination. RESULTS: Compared to the untreated scleral strips, the genipin-crosslinked scleral strips showed that the ultimate stress and Young's modulus at 10% strain were increased by the amplitude of 130% and 303% respectively, ultimate strain was decreased by 24%. There had no α-smooth muscle actin (α-SMA) positive cells in control and treated sclera. Histologically, there was no sign of apoptosis in the sclera, choroid, and retina; and no side effects were found in the peripheral cornea and optic nerve adjacent to the treatment area. CONCLUSION: Genipin induced crosslinking of collagen can increase its biomechanical behavior by direct strengthening of the extracellular matrix in rabbit sclera, with no α-SMA expression seen in the myofibroblasts. As there is no evidence of cytotoxicity in the scleral, choroidal, and retinal cells, genipin is likely a promising agent to strengthen the weakened sclera to prevent myopic progression.